Semen quality of male partners of infertile couples living with HIV infection - Ezechi, Oliver Chukwujekwu; Wapmuk, Agatha Eilleen; Ohihoin, Aigbe Greg; Otobo Ujah, Innocent Achanya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Infertility among HIV positive couples are increasingly been reported in various gynaecology clinic. Unfortunately research into aetiology of infertility is out tune with this emerging trend. This study was conducted to determine the semen quality among infertile HIV positive couples. Methods: A retrospective analysis of information obtained during routine care of infertile HIV positive couple at a large HIV treatment in Lagos Nigeria. Results: Over thirty percent (31.7%) of the male partners of HIV positive couple in study had abnormal semen quality. Secondary infertility was the commonest (79.2%). The quality of semen of the HIV negative men in the study was significantly better compared to that of HIV positive men (p<0.001). Of the five semen parameters compared, HIV positive participants with more severe diseases had significantly lower mean sperm volume (p=0.003), sperm concentration (p=0.0002) and total sperm concentration (p<0.001) compared to of HIV positive participants with less severe diseases . Approximately 22% of the semen of the men in this study was infected, with Staph aureus, E coli and Klebsiella being the most common microbial isolates. Conclusions: Male factor contributes about one third of infertility in this study and severity of HIV diseases impacts on semen quality. Further studies are needed to evaluate if antiretroviral therapy will reverse the effect of HIV infection on semen quality.